Concordance between Reticulocyte Hemoglobin Equivalent and Reticulocyte Hemoglobin Content in CKD Patients Undergoing Hemodialysis - Riadi Wirawan; Ailinda Theodora Tedja; Fify Henrika; Aida Lydia (Acta Medica Indonesiana, 2017)
Aim: to evaluate the correlation and the concordance between reticulocyte hemoglobin equivalent (RET-He) and reticulocyte hemoglobin content (CHr) as well as to obtain the cut-off value of RET-He as the target of iron supplementation in chronic kidney disease (CKD) patients undergoing hemodialysis. Methods: a cross-sectional study was performed using K3EDTA-anticoagulated peripheral blood samples collected from 106 CKD patients undergoing routine hemodialysis. The samples were then analyzed using both Sysmex XN-2000 and Siemens ADVIA 2120i for RET-He and CHr analysis. Results: a very strong correlation (r=0.91; p<0.0001) and a good concordance were found between RET-He and CHr with mean bias of 0.5 pg. The diagnostic concordance was 96.23%. The cut-off value of RET-He 29.2 pg was obtained from the receiver operating characteristic (ROC) curve with CHr as the gold standard. At this cut-off point, the sensitivity and specificity to assess the target of iron supplementation in CKD patients undergoing hemodialysis were 95.5% and 94%, respectively. Conclusion: the study shows a good correlation and concordance between RET-He and CHr in CKD patients undergoing hemodialysis.